2020
DOI: 10.29244/jji.v5i3.173
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Analysis of Antiviral Activity of Analog Curcumin Compounds

Abstract: Some studies state that curcumin analog compounds can improve the bioavailability and biological activity of curcumin. One of the methods to predict the bioactivity of curcumin was computational using molecular docking method. This study has done bioactivity tests of curcumin analog compounds as antiviral using the molecular docking method with the software used are PLANTS, YASARA, MarvinSketch, and Pymol for visualization. This study used analog curcumin compounds derived from previous research. This study us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
2
0
1
Order By: Relevance
“…According to [24], a compound can have a higher selectivity on the test receptor if the binding affinity of the test compound is lower than the control compound. The lower the binding affinity value, the stronger the binding force of the ligand to the receptor.…”
Section: Resultsmentioning
confidence: 99%
“…According to [24], a compound can have a higher selectivity on the test receptor if the binding affinity of the test compound is lower than the control compound. The lower the binding affinity value, the stronger the binding force of the ligand to the receptor.…”
Section: Resultsmentioning
confidence: 99%
“…Menurut Mulatsari et al (2020), suatu senyawa dapat memiliki selektivitas yang lebih tinggi pada reseptor uji jika binding affinity ikatan senyawa uji lebih rendah dari pada senyawa kontrol. Semakin rendah nilai binding affinity, semakin kuat gaya ikat ligan ke reseptor.…”
Section: Hasil Dan Pembahasanunclassified
“…Whereby the negative value of CHemPLP the increasingly strong bond between the receptor so that the affinity, the better. (Mulatsari et al, 2020).…”
Section: Curcumin Compoundsmentioning
confidence: 99%
“…Then in an in silico study, curcumin compounds showed immunostimulatory activity with an increase between the SARS-CoV 2 virus receptor causing hydrogen bonds and hydrophobic interactions that gave rise to good affinity. (Mulatsari et al, 2020). Therefore, the purpose of this systematic review was to examine the immunostimulant activity of turmeric rhizome in vitro, in vivo, and in silico and to explore the mechanism of curcumin compounds as immunostimulants.…”
Section: Introductionmentioning
confidence: 99%